Religious liberty : essays on First Amendment law - Robinson, Daniel N., 1937-; Williams, Richard N., 1950- (Cambridge University Press, 2016)
These essays focus on the intellectual and philosophical roots of religious liberty and the confrontations with the authority of secular law.